2013
DOI: 10.1017/s1047951113000516
|View full text |Cite
|
Sign up to set email alerts
|

Increased ischaemia-modified albumin is associated with inflammation in acute rheumatic fever

Abstract: The increased level of ischaemia-modified albumin in children with acute rheumatic fever seems to be associated with inflammation. However, further studies are needed to provide stronger evidence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 35 publications
0
9
0
Order By: Relevance
“…Karataş et al have found that the IMA levels were higher in the acute period and correlated with acute phase reactants in patients with acute rheumatic fever and that the levels were similar to healthy controls in the chronic period. It was suggested that the IMA levels might be associated with acute inflammation [33]. Among patients with Behcet' s disease, the IMA levels were found to increase in those with active disease and vascular involvement [34].…”
Section: Discussionmentioning
confidence: 99%
“…Karataş et al have found that the IMA levels were higher in the acute period and correlated with acute phase reactants in patients with acute rheumatic fever and that the levels were similar to healthy controls in the chronic period. It was suggested that the IMA levels might be associated with acute inflammation [33]. Among patients with Behcet' s disease, the IMA levels were found to increase in those with active disease and vascular involvement [34].…”
Section: Discussionmentioning
confidence: 99%
“…Ischemia‐modified albumin (IMA) is a new biochemical marker. It is associated with ischemia, inflammation, and oxidative stress 6 . Recently, high IMA levels have been determined in various inflammatory dermatological diseases such as psoriasis, alopecia areata, vitiligo, and Behçet's disease 7 .…”
Section: Introductionmentioning
confidence: 99%
“…In many diseases with oxidative stress in their etiology and with developed tissue perfusion damage, it has been indicated that IMA has increased and correlated with the disease activity . As far as we know, there is no study in the literature investigating the relation between IBD and IMA.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] In many diseases with oxidative stress in their etiology and with developed tissue perfusion damage, [6][7][8] it has been indicated that IMA has increased and correlated with the disease activity. 9,10 As far as we know, there is no study in the literature investigating the relation between IBD and IMA. Considering the relation of IMA with oxidative stress and tissue perfusion damage, we think that IMA might be related with the pathogenesis of IBD.…”
Section: Introductionmentioning
confidence: 99%